Medicaid and County Property Tax Levies on New York Farmland - Nelson L. Bills (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2004)
Changes in health care delivery and financing, along with shifting demographics, are reinventing health care institutions and market relationships in New York and throughout the United States. Many communities are struggling to provide health care services in ways that protect community economic interests and the health needs of local people. Local public officials, business interests, hospitals, and doctors in many communities are increasingly concerned about the capacity to provide quality products and services while delivering care at reasonable cost.
Keywords: 330; Gesetzliche Krankenversicherung; Sozialhilfeempfänger; Grundsteuer; Gemeindefinanzen; New York <Staat>